The Group Guidance Services to Normalize the Polite Behavior in Vocational High School Students - Aldila Fitri Radite Nur Maynawati; Siti Nur Khasanah; Supriyanto Supriyanto; Titik Tri Widati (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Polite behavior reflects students' character and personality at school and could indirectly affect student achievement. The primary purpose of this study is to analyze group guidance services to improve positive student behavior, using a case study of class X MPLB students at Vocational High School Tamansiswa Sukoharjo. The method used is qualitative descriptive analysis through questionnaires, observations, and group discussions. The results of the study indicated that personal interests considerably dominated 47.15% of students' life needs. While study, social, and career needs were 19.69%, 17.77%, and 16.39%, respectively. The results of student observations conducted before the group guidance service indicated that 18 students behaved in an impolite manner. After the group guidance service intervention, the number of students who behaved in an impolite manner decreased to 5. Impolite behavior among students included using impolite language (cursing), mocking (bullying), and dressing untidily. However, rude behavior among individuals tended to decrease significantly after the group guidance service. Therefore, group guidance services are highly effective in promoting positive behavior among students, and they could be widely applied in other schools. Keywords: group guidance, manners, morals, student, vocational high school